2019
DOI: 10.1130/ges02069.1
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary coral reef complexes as powerful markers of long-term subsidence related to deep processes at subduction zones: Insights from Les Saintes (Guadeloupe, French West Indies)

Abstract: Geodetic measurements reveal modern rates of tectonic deformation along subduction zones, but the kinematics of long-term deformation are typically poorly constrained. We explore the use of submarine coral reefs as a record of long-term coastal vertical motion in order to determine deformation rate and discuss its origins. The Lesser Antilles arc results from the subduction of the American plates beneath the Caribbean plate and undergoes regional vertical deformation. Uplifted reefs along forearc islands are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 100 publications
(159 reference statements)
2
23
0
Order By: Relevance
“…Some vertical movement assessments in this area were performed in the past. Paleo-geodesy based on coral reef growth tends to show a subsidence trend in Martinique and Les Saintes Islands (south of Guadeloupe archipelago) (Weil-Accardo et al 2016;Leclerc and Feuillet 2019). This subsidence is corroborated by GNSS observations for a few stations within the vertical velocity ULR6 solution (Santamaría-Gómez et al 2017).…”
Section: Introductionmentioning
confidence: 63%
“…Some vertical movement assessments in this area were performed in the past. Paleo-geodesy based on coral reef growth tends to show a subsidence trend in Martinique and Les Saintes Islands (south of Guadeloupe archipelago) (Weil-Accardo et al 2016;Leclerc and Feuillet 2019). This subsidence is corroborated by GNSS observations for a few stations within the vertical velocity ULR6 solution (Santamaría-Gómez et al 2017).…”
Section: Introductionmentioning
confidence: 63%
“…Although the closest of these study sites is about 100 km from the Kahouanne Seamounts, the fact that similar subsidence rates are observed between Guadeloupe and Martinique (separated by 170 km) suggests that regional subsidence is indeed impacting a large area of the northern Lesser Antilles, as suggested by Leclerc et al (2015). A detailed analysis of submerged coral reef complexes from Les Saintes (Guadeloupe) by Leclerc and Feuillet (2019) indicated that their configurations and present depths could only be explained by subsidence and not by westward tilting of the arc platform as evidenced by uplifted carbonate terraces in Grand Terre, Marie Galante and La Desirade. They considered a number of possible mechanisms to explain subsidence of the carbonate platforms including the influence of volcanic activity (magma chamber cooling, loading of volcanic edifices, changes in hydro-static pressures of deep magma chambers), active faulting, and long-term subduction processes.…”
Section: Evolution and Subsidence Of The Kahouanne Seamountsmentioning
confidence: 65%
“…Recent studies of drowned carbonate platforms off the islands of Guadeloupe and Martinique have revealed evidence for tectonic Distance (meters) Depth (meters below sealevel) subsidence with rates from 300 to 400 m/My, influenced by regional as well as local processes (Leclerc et al, 2014(Leclerc et al, , 2015Leclerc and Feuillet, 2019). Although the closest of these study sites is about 100 km from the Kahouanne Seamounts, the fact that similar subsidence rates are observed between Guadeloupe and Martinique (separated by 170 km) suggests that regional subsidence is indeed impacting a large area of the northern Lesser Antilles, as suggested by Leclerc et al (2015).…”
Section: Evolution and Subsidence Of The Kahouanne Seamountsmentioning
confidence: 99%
See 2 more Smart Citations